The pale horseman - Cornwell, Bernard (Cornwell, Bernard. Last kingdom, 2015)
Uhtred is a Saxon, cheated of his inheritance and adrift in a world of fire, sword, and treachery. He has to make a choice: whether to fight for the Vikings, who raised him, or for King Alfred the Great of Wessex, who dislikes him. In the late ninth century, Wessex is the last English kingdom. The rest have fallen to the Danish Vikings, a story told in The Last Kingdom, the New York Times bestselling novel in which Uhtred's tale began. Now the Vikings want to finish England. They assemble the Great Army, whose one ambition is to conquer Wessex. A dispossessed young nobleman, married to a woman who hails from Wessex, Uhtred has little love for either, though for King Alfred he has none at all. Yet fate, as Uhtred learns, has its own imperatives, and when the Vikings attack out of a wintry darkness to shatter the last English kingdom, Uhtred finds himself at Alfred's side. Bernard Cornwell's The Pale Horseman, like The Last Kingdom, is rooted in the real history of Anglo-Saxon England. It tells the astonishing and true story of how Alfred, forced to become a fugitive in a few square miles of swampland, fights his enemies against overwhelming odds. The king is a pious Christian, while Uhtred is a pagan. Alfred is a sickly scholar, while Uhtred is an arrogant warrior. Yet the two forge an uneasy alliance that will lead them out of the marshes to the stark hilltop where the last remaining Saxon army will fight for the very existence of England. Enthralling as both a historical and personal story, The Pale Horseman is a novel of divided loyalties and desperate heroism, featuring a cast of fully realized characters, from a king in despair to a beguiling British sorceress. And always, beyond the spearmen and the swordsmen are the folk who suffer as the tides of war sweep over their farmlands.